Shipwreck OR49 and the shipping of peat around the Zuiderzee area in the 17th century - Waldus, Wouter B. (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In this article the results of the excavation of a 17th century inland peat ship on lot OR49 in the IJsselmeerpolders are analyzed in a broad maritime historical context. Peat was the main source of energy in premodern times, and the economy of the cities of the Republic was dependent on these transport ships. Based on historical and geographical data the transport volume of peat is reconstructed and compared to other sectors of seafaring. Besides this, wreck OR49 offers a unique perspective on life on board of inland cargo ships during the Dutch Golden Age.